2021
DOI: 10.1017/cts.2021.883
|View full text |Cite
|
Sign up to set email alerts
|

A system-wide health sciences faculty mentor training program is associated with improved effective mentoring and institutional climate

Abstract: Introduction: Mentorship is critical for faculty success, satisfaction, and engagement. However, many faculty, particularly underrepresented racial/ethnic (UR) faculty, lack access to high-quality mentoring. In an effort to improve mentoring for all faculty, we developed and implemented a formally structured faculty mentor training program (FMTP) across UC San Diego Health Sciences, which included institutional support, mentorship training, and department/division mentorship programs. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Because the goal of the JAM Council is to explicitly address the effects of racism, biased practices, and structures that adversely impact UIM faculty, in addition to traditional outcome measures such as career satisfaction, attrition and length to promotion, measurement of minority tax burden, belonging, connectedness, wellbeing, and impostor syndrome will be conducted. Evaluations will be conducted at multiple time points and include mixed methods of qualitative and quantitative measures with the goal of generating a holistic perspective to provide robust assessment of program processes, outcomes and lessons learned (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the goal of the JAM Council is to explicitly address the effects of racism, biased practices, and structures that adversely impact UIM faculty, in addition to traditional outcome measures such as career satisfaction, attrition and length to promotion, measurement of minority tax burden, belonging, connectedness, wellbeing, and impostor syndrome will be conducted. Evaluations will be conducted at multiple time points and include mixed methods of qualitative and quantitative measures with the goal of generating a holistic perspective to provide robust assessment of program processes, outcomes and lessons learned (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Although effective mentoring is critical for academic success, there are limited studies documenting the structure and effectiveness of mentoring programs for UIM faculty (12,13). More recently, studies that include the implementation or evaluation of UIM mentoring programs that explicitly addresses common obstacles rooted in racist or biased practices and structures have been described (20)(21)(22)(23)(24). Research has found that mentorship programs for UIM faculty must assess for relevant elements that include mentors' potential for bias and discrimination, previous mentorship training, experience with intersectionality and isolation, and service on diversity committees, among other factors (20,21).…”
Section: Best Practices In Mentoring Programs For Uim Facultymentioning
confidence: 99%
See 1 more Smart Citation
“…Given the importance of mentorship in undergraduate research experiences, efforts have been made to increase the mentoring commitment and competency of STEMM faculty members. [10][11][12][13][14] Research has also uncovered key factors, such as open communication or frequent interaction, that contribute to effective mentoring relationships between faculty and undergraduate researchers. 5,[15][16][17][18][19] However, we currently know little about how similarities or differences in the social identities of mentors and mentees affect undergraduates' research experiences and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of mentorship in undergraduate research experiences, efforts have been made to increase the mentoring commitment and competency of STEMM faculty members 10–14 . Research has also uncovered key factors, such as open communication or frequent interaction, that contribute to effective mentoring relationships between faculty and undergraduate researchers 5 , 15–19 .…”
Section: Introductionmentioning
confidence: 99%